1997
DOI: 10.1037/0021-843x.106.3.491
|View full text |Cite
|
Sign up to set email alerts
|

Magical ideation and social anhedonia as predictors of psychosis proneness: A partial replication.

Abstract: ) report of heightened psychosis proneness in MagSoc individuals. The MagSoc group exceeded the control group on severity of psychotic-like experiences; ratings of schizotypal, paranoid, and borderline personality disorder symptoms; and rates of mood and substance use disorders. Two of the MagSoc participants but none of the control participants developed psychosis during the follow-up period (a nonsignificant difference). Consistent with L. J. Chapman et al.'s findings, the groups did not differ on rates of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
119
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(131 citation statements)
references
References 17 publications
9
119
1
2
Order By: Relevance
“…Thus, our present findings would extend the observations of potential protective brain mechanisms along the schizophrenia spectrum including healthy schizo typal populations. In addition to these considerations, such protective mechanisms may explain why even large longitudinal studies on participants with high MI scores, as undertaken by the Chapman group (Chapman et al, 1994;Kwapil et al, 1997), failed to convincingly predict a later psychotic breakdown from elevated positive schizotypal features alone (see also Verdoux and van Os, 2002). Indeed, high MI might also predict a later mood disorder (Chapman et al, 1994) and is a common feature not only of the schizophrenia spectrum disorders but also a symptom of some personality disorders (eg Lyons et al, 1995;Kwapil et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our present findings would extend the observations of potential protective brain mechanisms along the schizophrenia spectrum including healthy schizo typal populations. In addition to these considerations, such protective mechanisms may explain why even large longitudinal studies on participants with high MI scores, as undertaken by the Chapman group (Chapman et al, 1994;Kwapil et al, 1997), failed to convincingly predict a later psychotic breakdown from elevated positive schizotypal features alone (see also Verdoux and van Os, 2002). Indeed, high MI might also predict a later mood disorder (Chapman et al, 1994) and is a common feature not only of the schizophrenia spectrum disorders but also a symptom of some personality disorders (eg Lyons et al, 1995;Kwapil et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these considerations, such protective mechanisms may explain why even large longitudinal studies on participants with high MI scores, as undertaken by the Chapman group (Chapman et al, 1994;Kwapil et al, 1997), failed to convincingly predict a later psychotic breakdown from elevated positive schizotypal features alone (see also Verdoux and van Os, 2002). Indeed, high MI might also predict a later mood disorder (Chapman et al, 1994) and is a common feature not only of the schizophrenia spectrum disorders but also a symptom of some personality disorders (eg Lyons et al, 1995;Kwapil et al, 1997). Thus, positive schizotypy may be accompanied by a relative hyperdopaminergia, but yet reflects just one of the many DA-mediated variations of the human mind and personality (Horrobin, 1998;Previc, 1999) accompanied by distinct cognitive capacities (Gianotti et al, 2001;Weinstein and Graves, 2002) and, ultimately, an unusual way of perceiving the world (Wolfradt et al, 1999;Sto + ckenius and Brugger, 2000;McCreery and Claridge, 2002;Van de Ven and Merckelbach, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al (2006) examined patients who suffered relapses in psychosis and showed that those with worse depression, self-esteem, and negative beliefs, had persecutory delusions of greater severity. In healthy participants, two longitudinal studies reported that psychosis-prone individuals had a higher rate of Major Depressive Disorder than controls (Chapman et al, 1994;Kwapil et al, 1997) and were at a higher risk to develop an incident depression . Low selfesteem was also associated to delusional ideation in the general population (Warman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on schizotypy indicates that schizotypal symptoms divide into the same three factors found in schizophrenia, ie positive, negative, and disorganized (Reynolds et al, 2000;Suhr and Spitznagel, 2001). Here, we chose to focus on the positive and negative dimensions of schizotypy, since these have been associated in longitudinal studies with elevated rates of psychosis and social dysfunction (Erlenmeyer-Kimling et al, 1993;Chapman et al, 1994;Kwapil et al, 1997;Freedman et al, 1998). We identified positive and negative symptom schizotypy using the perceptual aberration (PerAb) and physical anhedonia (PhysAn) scales, respectively (Chapman et al, 1976(Chapman et al, , 1978.…”
Section: Introductionmentioning
confidence: 99%